IN SITU INVESTIGATION OF DISSOLUTION OF HEAVY METAL CONTAINING MINERAL PARTICLES IN AN ACIDIC FOREST SOIL - Birkefeld A.; Schulin R.; Nowack B. (My University, 2006)
We report the application of an in situ method to obtain field dissolution rates of fine mineral particles in soils. Samples with different metal-containing mineral and slag particles (lead oxide, copper concentrate and copper slag) from the mining and smelting industry were buried in the topsoil of an acidic forest soil for up to 18 months. In addition we studied the dissolution of these particles in samples of the same soil, in a sand matrix and in acid solution under constant temperature and moisture conditions in the laboratory. Under field conditions the PbO particles dissolved quite rapidly (2.4 ? 0.7 ? 10-10 mol Pb m-2 s-1), whereas the copper concentrate (<1 ? 10-11 mol Cu m-2 s-1) and the copper slag particles (4.3 ? 0.8 ? 10-11 mol Cu m-2 s-1) proved to be more resistant to weathering. In addition to qualitative information on dissolution features (SEM), the method yielded quantitative data on in situ dissolution rates. The dissolution rates followed the order: sand with acid percolation (pH 3.5; lab) < soil (lab) < soil (field) < acid solution (pH 3.5; lab). Dissolution rates in soil were found to be lower under laboratory than under field conditions. The faster field rates may in part be attributed to the higher biological activity in the field soil compared to the same soil in the laboratory. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ACID SOIL; DISSOLUTION; FOREST SOIL; HEAVY METAL